Tryptophan auxotroph mutants suppress the superroot2 phenotypes, modulating IAA biosynthesis in arabidopsis - Kiyohara, Shunsuke (Landes Bioscience, 2011)
Plant phytohormone, Indole-3-acetic acid (IAA ), is synthesized by tryptophan (trp) dependent and independent pathway. Here we report that tryptophan auxotroph mutants completely suppressed the abnormalities of auxin over production mutant, superroot2. SUR2 is considered to modulate Trp dependent pathway, resulting IAA accumulation in Arabidopsis. Tryptophan auxotroph mutants showed hyper-sensitivity to the auxin polar transport inhibitor, NPA, on the phenotype of reduced gravitropism. These results together with the results of histochemical analyses, tryptophan auxotroph mutants seem to have a complete defect in Trp dependent IAA biosynthesis pathway, and it is also suggested that the Trp dependent pathway is responsible for the normal root gravitropism.